Bank Risk and Deposit Insurance - Laeven, Luc (2014)
Arguing that a relatively high cost of deposit insurance indicates that a bank takes excessive risks, this article estimates the cost of deposit insurance for a large sample of banks in 14 economies to assess the relationship between the risk-taking behavior of banks and their corporate governance structure. The results suggest that banks with concentrated ownership tend to take the greatest risks, and those with dispersed ownership engage in a relatively low level of risk taking. Moreover, as a proxy for bank risk, the cost of deposit insurance has some power in predicting bank distress